The Complex Bidirectional Relationship Between Depression and Cardiovascular Disease - Robak, Jakub; Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika (Quality in Sport, 2025)
This systematic review establishes a robust bidirectional relationship between depression and cardiovascular disease (CVD) mediated by interconnected biological pathways including autonomic dysfunction, chronic inflammation, and endothelial impairment. Depression significantly increases CVD risk while CVD elevates depression susceptibility, creating a self-perpetuating cycle with worse clinical outcomes. Women with CVD demonstrate particular vulnerability to depression, necessitating gender-sensitive approaches. Current evidence supports integrated management strategies incorporating routine depression screening, selective serotonin reuptake inhibitors (SSRIs) like sertraline, and cognitive-behavioral therapy within cardiac care. However, optimal treatment requires addressing both conditions simultaneously through collaborative care models. Future research priorities include elucidating causal mechanisms, developing biomarkers for risk stratification, and testing interventions targeting shared pathways. These findings underscore the urgent need for healthcare systems to implement holistic approaches that bridge mental and cardiovascular health, ultimately improving outcomes for this high-risk population.